Capacity Building of Youth Through Technical Vocational Education and Training for Sustainable Development in Federal Universities in South-South Nigeria - Ogbebor, Samuel Osamede; Oviawe, Jane (Innovare Journal of Education, 2025)
This study investigated the capacity building of youth through technical vocational education and training for sustainable development in a Federal University in South-South Nigeria. Two research questions and one hypothesis guided the study. The study adopted a cross-sectional survey design and was conducted in three Federal Universities in South-South Nigeria, using a convenient random sampling technique. The study population was 120 TVET educators, comprising 85 lecturers and 35 instructors. A structured questionnaire titled Capacity Building of Youth through Technical Vocational Education and Training for Sustainable Development (CBYTVETSD) was used for data collection by the researcher with the support of two research assistants. The instrument was validated by three research experts, two from the Department of Vocational and Technical Education, Ambrose Alli University, and one from Measurement and Evaluation, University of Benin, both in Edo State, Nigeria. Cronbach Alpha reliability was used and an overall reliability coefficient of 0.81 was achieved. Data were analyzed using mean, standard deviation, and t-test to test the hypothesis at 0.05 significance level. Generally, studies found that the role and impact of TVET programs are essential for sustainable development. The study concluded that capacity building of youths through TVET for sustainable development is essential for the effective reduction of hunger, poverty, unemployment, and dependency among youth and that it aids in the promotion of competent manpower development, creative skills, job creation, self-employment, self-reliant, gainful employment, fast rack technology process, life- long learning among others. The paper recommended the need for conducting public education campaigns and activities to educate and inform communities about the significance of TVET programs and that effective co-ordination and co-operation of TVET programs should be encouraged between the responsible bodies for sustainable development, among others.